Sntrusntm i7 captikwlh: Unravel the Story, the Okanagan Way - Ragoonaden, Karen; Cherkowski, Sabre; Baptiste, Maxine; Després, Blane (Alberta Journal of Educational Research, 2010)
This study raises the question of how the Canadian educational system can avoid promoting cultural or ideological racism in a student population that is increasingly Indigenous and immigrant. It responds to this question by pointing to the need to expand knowledge systems in teacher education programs, presenting a multi-thematic discussion that explores how contemporary ways of teaching and learning can be transformed into a diverse, sustainable, and global curriculum. The focus of the article is on school culture, specifically the Aboriginal way of knowing about language-learning, creating multicultural teachers, leadership for a culture of inclusion and diversity, and the idea of resistance to change.